Knowledge and Performance about Nursing Ethic Codes from Nurses' and Patients' Perspective in Tabriz Teaching Hospitals, Iran - Mohajjel-Aghdam, Alireza (Tabriz University of Medical Sciences, 2013)
Introduction: Nursing profession requires knowledge of ethics to guide performance. The nature of this profession necessitates ethical care more than routine care. Today, worldwide definition of professional ethic code has been done based on human and ethical issues in the communication between nurse and patient. To improve all dimensions of nursing, we need to respect ethic codes. The aim of this study is to assess knowledge and performance about nursing ethic codes from nurses' and patients' perspective. Methods: A descriptive study Conducted upon 345 nurses and 500 inpatients in six teaching hospitals of Tabriz, 2012. To investigate nurses' knowledge and performance, data were collected by using structured questionnaires. Statistical analysis was done using descriptive and analytic statistics, independent t-test and ANOVA and Pearson correlation coefficient, in SPSS(13). Results: Most of the nurses were female, married, educated at BS degree and 86.4% of them were aware of Ethic codes also 91.9% of nurses and 41.8% of patients represented nurses respect ethic codes. Nurses' and patients' perspective about ethic codes differed significantly. Significant relationship was found between nurses' knowledge of ethic codes and job satisfaction and complaint of ethical performance. Conclusion: According to the results, consideration to teaching ethic codes in nursing curriculum for student and continuous education for staff is proposed, on the other hand recognizing failures of the health system, optimizing nursing care, attempt to inform patients about Nursing ethic codes, promote patient rights and achieve patient satisfaction can minimize the differences between the two perspectives.